The Effect of Phosphate Fertilizer and Lime in Ultisol Soil on Phosphate and Protein Leaf Levels of Corn (Zea mays L.) and Soybean (Glycine max L. (Merr)) - Silahooy, Charles (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Effect of Phosphate Fertilizer and Lime in Ultisol Soil on Phosphate and Protein Leaf Levels of Corn (Zea mays L.) and Soybean (Glycine max L. (Merr))